Residents’ Opinions on Apartment Living in Lahore, Pakistan - Tehniyat Fatima (Asian Journal for Public Opinion Research, 2021)
Vertical growth is viewed as the solution to the problem of urban housing. The present study aims to be multifocal in approaching the phenomenon of apartment living in Lahore, Pakistan. The primary focus of the research was to evaluate the satisfaction with and favorability of vertical living among the dwellers; however, the research was extended to include the in-depth experiences of adolescents regarding privacy because it was observed that this age group was being neglected severely in the distribution of privacy in apartments, as well as in research. The data was first collected from 150 respondents through a survey, and then interviews of 10 adolescents were conducted to explore notion of privacy. The findings highlight that, despite being satisfied with the infrastructural aspects of the building, the residents do not prefer vertical living over horizontal housing. The adolescents in apartments also prefer horizontal housing over vertical living to avoid the feeling of crowdedness that is associated with vertical growth due to shared space and proximity. The utilization of spaces within apartments is associated with certain elements of development of the personality during this age. The findings of the present study can be helpful for sustainable vertical housing policy development and implementation.